2019
DOI: 10.3390/geriatrics4040067
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Dysphagia after Stroke: An Interview Study of Stroke Survivors and Their Informal Caregivers

Abstract: (1) Background: Swallowing difficulties (dysphagia) after stroke are not uncommon and is a consistent risk factor for stroke-associated pneumonia. This interview study explores the perspectives of stroke survivors, who had their swallowing assessed in the first few days of admission to hospital, and their informal caregivers. (2) Methods: A participatory approach was used involving people affected by stroke in the interpretation and analysis of the interview data. Data was thematically analysed and six themes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Role changes were also found in dysphagia caregivers. A few qualitative studies explored the experience of caregivers, and the results were also in line with some evidence found in our study (Eltringham et al, 2019; Lisiecka et al, 2020). One study demonstrated that caregivers of patients with dementia and dysphagia also experienced changes in emotions and roles (Howells et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Role changes were also found in dysphagia caregivers. A few qualitative studies explored the experience of caregivers, and the results were also in line with some evidence found in our study (Eltringham et al, 2019; Lisiecka et al, 2020). One study demonstrated that caregivers of patients with dementia and dysphagia also experienced changes in emotions and roles (Howells et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…After careful examination of the full texts, 5 studies were included for further synthesis (Carlsson et al, 2004; Helldén et al, 2018; Kjaersgaard & Pallesen, 2020; Medin et al, 2010; Moloney & Walshe, 2018). Two studies were excluded because they explored the experiences of not only dysphagia patients but also caregivers and other stakeholder groups, and dysphagia experience could not be extracted (Eltringham et al, 2019; Shune & Linville, 2019). The search results and process are illustrated in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Swallowing disorders are impairing social life [10] and are facilitating anxiety and depression [11]. Emotional and subjective impact of dysphagia have been described in qualitative investigations [12][13][14], have psychosocial effect on families [15,16], and are impairing life quality [17,18]. Despite this and inclusion of some emotional aspects in recent scores [19], little has been published about a holistic assessment of emotions and family interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Eltringham et al. (2019) found that even in the early stages, participants’ past–future experiences influenced their emotional responses to events around onset of dysphagia. This suggests that healthcare providers should make a concerted effort to understand the caregivers’ perceptions of their loved‐one's dysphagia in order to provide tailored information and education that addresses issues around health and eating and drinking from a shared viewpoint.…”
Section: Discussionmentioning
confidence: 99%